2007
DOI: 10.1097/01.brs.0000259072.14859.d9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Back Pain Prevention Program

Abstract: This study provides no evidence for the adoption of this worksite prevention program for LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In accordance with previous studies on work ability (11,45,46) and mental and physical health status (47), the intervention in the current study showed no improvements on these outcomes. The lack of statisti-Effectiveness of a prevention program at construction worksites cally significant results in the present study are in line with the findings of the short-term outcomes (ie, social support, need for recovery, work engagement, and physical workload) that were also not statistically significant in favor of the intervention group (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In accordance with previous studies on work ability (11,45,46) and mental and physical health status (47), the intervention in the current study showed no improvements on these outcomes. The lack of statisti-Effectiveness of a prevention program at construction worksites cally significant results in the present study are in line with the findings of the short-term outcomes (ie, social support, need for recovery, work engagement, and physical workload) that were also not statistically significant in favor of the intervention group (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…Both outcomes distinctively assessed the physical status of the construction workers but concerned different aspects (ie, daily limitations in physical functioning versus musculoskeletal symptoms). We found several intervention studies among workers with physically demanding jobs that implemented an integrated approach of several components (eg, group training session, individual education, and exercises) and investigated the effects on musculoskeletal symptoms (45,47,51). All these studies failed to show a significant intervention effect on musculoskeletal symptoms as well.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Steel et al 39-42, 45-49, 51-54, 56-58, 60-75, 77-91, 93-128) Source absenteeism Firm data 26 (45, 46, 54, 57, 67-69, 71, 85, 86, 88, 91, 95, 96, 100, 101, 105, 107, 110, 114-116, 119, 125-127 (39, 42,49,51,56,57,62,64,66,72,78,79,81,82,87,89,94,102,104,109,113,117,118,(121)(122)(123)) Previous studies 10 (52, 53, 60, 61, 63, 83, 84, 99, 111, 120) Insurance data 9 (47, 48, 58, 60, 74, 75, 80, 112, 124 39, 42,49,56,72,79,81,82,102,104,109,117 11 (41, 56, 62, 93, 100, 107, 118, 119, 121-123) Estimated by the author 1 (88) The Chartered Institute of Personnel and Development 1 (108)…”
mentioning
confidence: 99%
See 1 more Smart Citation